If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5+4(n-9)=-3
We simplify the equation to the form, which is simple to understand
5+4(n-9)=-3
Reorder the terms in parentheses
5+(+4n-36)=-3
Remove unnecessary parentheses
+5+4n-36=-3
We move all terms containing n to the left and all other terms to the right.
+4n=-3-5+36
We simplify left and right side of the equation.
+4n=+28
We divide both sides of the equation by 4 to get n.
n=7
| 2+p=15 | | N/6-6=0 | | x-19=-4 | | 31+4t-t=30 | | 2x/4+2=5x+43 | | 8x+2x+40=360 | | a+18=17 | | -9(6x+9)+7=0 | | 2x-1=45 | | 4x-4+3x=-36 | | 2(4x-10)+10(x+2)=360 | | 6x+4=10+3x | | 78/9+55/6 | | r+-10=-23 | | 2/3-61/125 | | x/2-1/1+3x/4=-9/1 | | C/4+10-22 | | 1/10+4/15 | | k+-18=-33 | | -17-6k=6(1+3k) | | 2/5x-8/25x | | 4x+2y=74 | | 4(2+15)+2x=360 | | 5/8+0/1 | | 204=57z | | -15+x=-1 | | (4x^5-3x^4)/(5x^2) | | 18/13/13 | | 2/3x+1/10=-1/3x-1/3 | | 34a=272 | | -19n=-57 | | 5x-3-9+6=45 |